National Private Television Network Competition based on Local Information Programs - Atika, Atika; Maulina, Novaria; Chandrabuwono, Achmad Bayu (Universitas Semarang, 2022)
Introduction: In the ecological analysis of television media, researchers determine the category of supporting sources (niche breadth) of media and measure the level of competition (niche overlap) of media based on local content-based information programs on networked national private television in South Kalimantan. Methods: This research employs a quantitative approach by collecting the data through observation of the program broadcasted by each television, then classifying into the instrument table and recording the results of the observations. The data is processed using the niche breadth and niche overlap formulas. Findings: The findings show that niche breadth 16 national private television media networks in South Kalimantan based on local content-based information programs are included in the specialist category with a niche breadth value of <3.5, which indicates that all television media have supporting resources but quite limited in showing local content-based information programs. Niche overlap of national private television network media based on local content-based information programs in South Kalimantan, there are 4 television paired stations that have a high level of competition compared to other paired stations: Global TV Banjarmasin and Net Banjarmasin; Global TV Banjarmasin and RTV Banjarmasin; Net Banjarmasin and RTV Banjarmasin; and SCTV Banjarmasin and Inspira TV Banjarmasin with a niche overlap value equal to 0.000.Originality: There is no publication with the same research result regarding competition for networked national private television. This is what makes this article fulfill the element of originality, which specifically analyzes television competition based on local information program broadcasts.